Effect of ICU care bundles on long-term patient-relevant outcomes: a scoping review. Issue 2 (17th February 2023) - Paul, Nicolas; Ribet Buse, Elena; Knauthe, Anna-Christina; Nothacker, Monika; Weiss, Björn; Spies, Claudia D
Abstract : Objective: Care bundles are considered a key tool to improve bedside quality of care in the intensive care unit (ICU). We explored their effect on long-term patient-relevant outcomes. Design: Systematic literature search and scoping review. Data sources: We searched PubMed, Embase, CINAHL, APA PsycInfo, Web of Science, CDSR and CENTRAL for keywords of intensive care, care bundles, patient-relevant outcomes, and follow-up studies. Eligibility criteria: Original articles with patients admitted to adult ICUs assessing bundle implementations and measuring long-term (ie, ICU discharge or later) patient-relevant outcomes (ie, mortality, health-related quality of life (HrQoL), post-intensive care syndrome (PICS), care-related outcomes, adverse events, and social health). Data extraction and synthesis: After dual, independent, two-stage selection and charting, eligible records were critically appraised and assessed for bundle type, implementation strategies, and effects on long-term patient-relevant outcomes. Results: Of 2012 records, 38 met inclusion criteria; 55% (n=21) were before–after studies, 21% (n=8) observational cohort studies, 13% (n=5) randomised controlled trials, and 11% (n=4) had other designs. Bundles pertained to sepsis (n=11), neurocognition (n=6), communication (n=4), early rehabilitation (n=3), pharmacological discontinuation (n=3), ventilation (n=2) or combined bundles (n=9). Almost two-thirds of the studies reported on survival (n=24), 45% (n=17) on care-related outcomes (eg, discharge disposition), and 13% (n=5) of studies on HrQoL. Regarding PICS, 24% (n=9) assessed cognition, 13% (n=5) physical health, and 11% (n=4) mental health, up to 1 year after discharge. The effects of bundles on long-term patient-relevant outcomes was inconclusive, except for a positive effect of sepsis bundles on survival. The inconclusive effects may have been due to the high risk of bias in included studies and the variability in implementation strategies, instruments, and follow-up times. Conclusions: There is a need to explore the long-term effects of ICU bundles on HrQoL and PICS. Closing this knowledge gap appears vital to determine if there is long-term patient value of ICU bundles.